Prevalence of dental caries and treatment needs in children in coastal areas of West Bengal - Das, Dulal (Medknow Publications & Media Pvt Ltd, 2013)
OBJECTIVE: This study was carried out to measure the caries prevalence and treatment needs in school children of 6-14 year old residing in coastal areas of West Bengal. MATERIALS AND METHODS: A total of 1764 children of 6-14 years age group, studying in different primary and high schools of the coastal areas were examined using World Health Organization criteria (1997) to record the prevalence of dental caries. The treatment needs were also calculated according to that given criteria. STATISTICAL ANALYSIS: The results were subjected to statistical analysis using the Chi-square test and unpaired ‘t’ test. RESULTS: Dental caries were founded low in the studied population. The overall all caries prevalence in the permanent dentition was 28.06%, in boys it was 25.39% and in girls it was 30.86%. Therefore caries prevalence in female was higher and which was statistically highly significant (P < 0.05). The most frequently required treatment was one surface filling followed by other treatments irrespective of sex and age group. DISCUSSION: The presence of sea foods containing high fluoride and least availability of refined carbohydrate in the diet may be the reason of lower prevalence. CONCLUSION: child oral health is always a matter of concern for a developing country so further research is required to explore actual causes.